Vertebral formula and congenital abnormalities of the vertebral column in rabbits - Proks, P; Stehlik, L; Nyvltova, I; Necas, A; Vignoli, M; Jekl, V (Veterinary journal (London, England, 2018)
The aim of this retrospective study of 330 rabbits (164 males, 166 females) was to determine different vertebral formulas and prevalence of congenital vertebral anomalies in rabbits from radiographs of the cervical (C), thoracic (Th), lumbar (L) and sacral (S) segments of the vertebral column. The number of vertebrae in each segment of vertebral column, position of anticlinal vertebra and localisation and type of congenital abnormalities were recorded. In 280/330 rabbits (84.8%) with normal vertebral morphology, seven vertebral formulas were identified: C7/Th12/L7/S4 (252/330, 76.4%), C7/Th12/L6/S4 (11/330, 3.3%), C7/Th13/L7/S4 (8/330, 2.4%), C7/Th12/L7/S5 (4/330, 1.2%), C7/Th12/L8/S4 (3/330, 0.9%), C7/Th12/L7/S6 (1/330, 0.3%) and C7/Th11/L7/S4 (1/330, 0.3%). The anticlinal vertebra was identified as Th10 in 56.4% of rabbits and Th11 in 42.4% of rabbits. Congenital spinal abnormalities were identified in 50/330 (15.2%) rabbits, predominantly as a single pathology (n=44). Transitional vertebrae represented the most common abnormalities (n=41 rabbits) in the thoracolumbar (n=35) and lumbosacral segments (n=6). Five variants of thoracolumbar transitional vertebrae were identified. Cervical butterfly vertebrae were detected in three rabbits. One rabbit exhibited three congenital vertebral anomalies: cervical block vertebra, thoracic hemivertebra and thoracolumbar transitional vertebra. Five rabbits exhibited congenital vertebral abnormalities with concurrent malalignment, specifically cervical kyphosis/short vertebra (n=1), thoracic lordoscoliosis/thoracolumbar transitional vertebrae (n=1), thoracic kyphoscoliosis/wedge vertebrae (n=2) and thoracolumbar lordoscoliosis/thoracolumbar transitional vertebrae/lumbosacral transitional vertebrae (n=1). These findings suggest that vertebral columns in rabbits display a wide range of morphologies, with occasional congenital malformations.
Keywords: křížová kost; skolióza; bederní obratle; Retrospective Studies; Rabbit; Radiography; mužské pohlaví; Transitional vertebra; Thoracic Vertebrae; Congenital anomaly; kyfóza; Sacrum; ženské pohlaví; radiografie; zvířata; retrospektivní studie; králíci; Scoliosis; Rabbits; hrudní obratle; krční obratle; Kyphosis; Female; Cervical Vertebrae; Lumbar Vertebrae; Spine; Male; Animals